2018
DOI: 10.1016/j.vaccine.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Micro-planning for immunization in Kaduna State, Nigeria: Lessons learnt, 2017

Abstract: BackgroundThe OPV 3 coverage for Kaduna State, 12–23 months old children was 34.4%. The low OPV 3 coverage, due mainly to weak demand for routine antigens and the need to rapidly boost population immunity against the disabling Wild Polio Virus (WPV), led the Global Polio Eradication Initiatives (GPEI) to increase supplemental OPV campaigns in Kaduna State, despite the huge cost and great burden on personnel. The OPV campaigns, especially in high risk (low vaccine uptake, <80% OPV 3 coverage and high vaccines r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Poor immunisation system performance often highlights underlying structural weaknesses in the health system in which it operates 29. Issues of poorly financed health systems,30 31 demotivated human resource for health32 and poor planning for immunisation within the wider context of the health system33 have been reported in Mali, Guinea and Nigeria as contributory to poor coverages and dropout. However, the above factors can only partially explain the poor performance in these countries, as other relatively well-performing countries in the subregion also grapple with similar challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Poor immunisation system performance often highlights underlying structural weaknesses in the health system in which it operates 29. Issues of poorly financed health systems,30 31 demotivated human resource for health32 and poor planning for immunisation within the wider context of the health system33 have been reported in Mali, Guinea and Nigeria as contributory to poor coverages and dropout. However, the above factors can only partially explain the poor performance in these countries, as other relatively well-performing countries in the subregion also grapple with similar challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The figures are, however, not reliable due to an underestimated denominator and data quality issues. 7 , 8 The poor immunization data quality increasingly makes the use of survey data more valuable for critical decision-making and immunization performance review.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Kaduna State, northwestern Nigeria showed that the projected census population that was used to compute RI denominator was fraught with errors and a gross underestimate of the target population (denominator) for RI when compared with a carefully conducted mini-census (ie, microplanning and walk-through). 17 Nevertheless, a scrutiny of the RI coverage trend for BCG, Penta 1, Penta 3, and measles from January to September 2019, depicted a bit of an undulating pattern. There was a modest increase in coverage during the months when SIAs rounds were integrated with routine immunization.…”
Section: Discussionmentioning
confidence: 99%